2022
DOI: 10.1097/bpo.0000000000002184
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of “Sleeper Plate” in Temporary Hemiepiphysiodesis and the Observation of “Tethering”

Abstract: Background: Guided growth is commonly performed by placing an extraperiosteal 2-hole plate across the growth plate with one epiphyseal and one metaphyseal screw. Recent studies investigated the efficacy of the removal of the metaphyseal screw only (sleeper plate) after correction. They concluded the practice to be unnecessary as only 19% of patients showed recurrence of deformity. This study aims to examine the incidence of rebound and undesired bony in-growth of the plate (tethering) after metaphyseal screw r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
11
1
Order By: Relevance
“…They note a 22% rate of rebound requiring replacement of the screw, and 2 complications (1 soft tissue irritation, 1 progression of angular deformity), both of which required unplanned surgery. Taken together, these 2 studies2,3 and that of the authors1 show the common theme of complications of this technique and the need for unnecessary surgery. With this information, removal of only the metaphyseal screw seems to be high risk, low reward, and should not be recommended for routine use based on the available evidence.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…They note a 22% rate of rebound requiring replacement of the screw, and 2 complications (1 soft tissue irritation, 1 progression of angular deformity), both of which required unplanned surgery. Taken together, these 2 studies2,3 and that of the authors1 show the common theme of complications of this technique and the need for unnecessary surgery. With this information, removal of only the metaphyseal screw seems to be high risk, low reward, and should not be recommended for routine use based on the available evidence.…”
mentioning
confidence: 74%
“…I do appreciate that the authors acknowledge the potential complications of removing only the metaphyseal screw 1. Concerns regarding the possibility of harm using this technique have been raised previously in at least 2 studies 2,3.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The results of another study revealed a higher incidence of rebound with faster correction speeds and following tension band plating for growth modulation compared with transphyseal screw hemiepiphysiodesis 56 . Gerges et al reported a 36% rebound rate and a 16% incidence of tethering and undesired continuation of growth modulation in a cohort of patients in whom a guided-growth implant for angular deformity correction around the knee had been converted to a sleeper plate by removal of the metaphyseal screw 57 .…”
Section: Guided Growthmentioning
confidence: 99%